2023
DOI: 10.1111/liv.15579
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of HDV: Epidemiologic implications and public health perspectives

Abstract: Hepatitis delta virus (HDV) infection causes the severest form of viral hepatitis in humans. Discovered in 1977, it was considered an infection prevalent in the eastern Mediterranean region. Today it is recognized as a global infection of public health importance, however accurate prevalence remains uncertain because of lack of good epidemiological studies. Under‐screening for HDV is the single most important factor in under‐estimating the true burden of infection. Urgent efforts are therefore needed to apply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…NAT NDR samples (327/368; 88.9%) were also included, as it has previously been shown that HBV DNA carriage can be confirmed by extended testing in around 66% of cases [ 17 ]. In addition, underscreening for HDV markers in HBV carriers with no detectable HBsAg may lead to a significant underestimation of the global HDV prevalence [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…NAT NDR samples (327/368; 88.9%) were also included, as it has previously been shown that HBV DNA carriage can be confirmed by extended testing in around 66% of cases [ 17 ]. In addition, underscreening for HDV markers in HBV carriers with no detectable HBsAg may lead to a significant underestimation of the global HDV prevalence [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their dedicated review article of this special issue, Tharwani and Hamid discuss the requirements on a global scale and nicely describe more specific needs depending on the HDV prevalence and affected population. 44 Another important task will be the further improvement of HDV therapy. As discussed before, there remain several unanswered questions regarding the current treatment option with bulevirtide ± Peg-IFN.…”
Section: Ne X Ts Tepsinhepatitisdeltamentioning
confidence: 99%